2019
DOI: 10.1017/s1047951119000830
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation of left posterior fascicular ventricular tachycardia in children with limited fluoroscopy exposure

Abstract: Introduction:Catheter ablation of left posterior fascicular ventricular tachycardia in the pediatric population remains challenging, and most studies about this topic have been conducted on adult patients. This study aimed to assess the clinical presentation features and outcomes of catheter ablations performed using limited fluoroscopy with three-dimensional electroanatomic mapping system guidance in a pediatric left posterior fascicular ventricular tachycardia patient group.Methods:A total of 20 consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…A recurrence rate of 20% and 3% was recorded during short-and long-term follow-ups. Repeat ablations achieved permanent success in all cases 24,25 . Only the last four cases were performed in our series with 3-D mapping after introducing this technology in our center.…”
Section: Interventional Treatmentmentioning
confidence: 83%
See 1 more Smart Citation
“…A recurrence rate of 20% and 3% was recorded during short-and long-term follow-ups. Repeat ablations achieved permanent success in all cases 24,25 . Only the last four cases were performed in our series with 3-D mapping after introducing this technology in our center.…”
Section: Interventional Treatmentmentioning
confidence: 83%
“…In a small series of four patients with a mean age of 14.5 years (4-20 years), success was achieved in all cases using noncontact mapping (EnSite ArrayTM) 23 . Two recent studies with EnSite NavXTM totaling 53 children reported an acute success rate of 95% and 100%, with a median fluoroscopy time between 1.25 and 5.1 minutes 24,25 , although fluoroscopy was not used in 91% of cases 23 .…”
Section: Interventional Treatmentmentioning
confidence: 99%
“…Twenty-five patients were male, and eight were female. The mean weight of the patients was 39.6 ± 10.4 kg (22-86), and the mean age was 13.6 ± 2.5 years (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The indication for ablation was decreased left ventricular systolic function, revealed by echocardiography (EF: 45%) in one patient due to incessant fascicular tachycardia.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is limited experience in the use of mapping systems in paediatric patients with fascicular tachycardia, and conventionally, X-rays have been used for catheter navigation during these procedures. 8,9 It is known that children are very susceptible to ionising radiation beginning from fetal life. [10][11][12][13] Therefore, radiation exposure should be minimised in paediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation